Multimodal vs. Text-Only Models on MATH Benchmark Performance - Assignee Research (Assignee Research, 2026)
This report synthesises findings from 13 peer-reviewed papers addressing the following research question: How does the performance of multimodal models trained on both textual and symbolic mathematical representations compare to text-only models on the MATH dataset. 10 claims were extracted from source literature; 2 were independently verified against retrieved documents. An automated multi-reviewer quality assessment produced a score of 4.5/10. This report is a machine-generated literature synt
Machine-generated literature synthesis.